3D Map Project in Collaborative Learning: Solution for Improving Geography Learning Outcomes - Prisma Wahyudi; Yusuf Suharto; Ahmad Irfan Ardiansyah (JPG (Jurnal Pendidikan Geografi), 2025)
The current traditional learning model has many shortcomings. Collaborative Project-Based Learning (CPjBL) is a learning model that combines Collaborative Learning and Project-Based Learning, with an emphasis on the innovative collaboration aspect of students. This research aims to test the effectiveness of the CPjBL learning model on XII-B2 class students in geography subjects, especially the material on urban, rural, and transitional areas. This research applied the Classroom Action Research (CAR) method. The research subjects consisted of 35 students of class XII-B2 at SMA Negeri 1 Tulungagung. Data were collected through tests and non-tests for two cycles to measure the improvement of students' learning outcomes. The model tested was Collaborative Project-Based Learning with a 3D Map Project. The result showed that applying the CPjBL model with the 3D Map project positively affected student learning outcomes, with a significant increase from cycle I to cycle II. This improvement can be seen from the increase in students' average score from 65.5 to 81,3 and the percentage of learning completeness from 25.7% to 77.1%. The application of the Collaborative Project-Based Learning model through the 3D Map project has proven to improve student learning outcomes. This model encourages student collaboration in finding innovations and creative ideas to visualize the characteristics of urban and rural areas effectively.